Understanding the Economic Impact of Health Care-Associated Infections: A Cost Perspective Analysis. Issue 2 (March 2019) - Scott, R. Douglas; Culler, Steven D.; Rask, Kimberly J.
Abstract : The economic impacts from preventing health care-associated infections (HAIs) can differ for patients, health care providers, third-party payers, and all of society. Previous studies from the provider perspective have estimated an economic burden of approximately $10 billion annually for HAIs. The impact of using a societal cost perspective has been illustrated by modifying a previously published analysis to include the economic value of mortality risk reductions. The resulting costs to society from HAIs exceed $200 billion annually. This article describes an alternative hospital accounting framework outlining the cost of a quality model which can better incorporate the broader societal cost of HAIs into the provider perspective.